Are professional young rugby league players eating enough? Energy intake, expenditure and balance during a pre-season - Costello, N.; Deighton, K.; Preston, T.; Matu, J.; Rowe, J.; Jones, B. (European Journal of Sport Science, 2019)
Due to the unique energetic demands of professional young collision sport athletes, accurate assessment of energy balance is required. Consequently, this is the first study to simultaneously investigate the energy intake, expenditure and balance of professional young rugby league players across a pre-season period. The total energy expenditure of six professional young male rugby league players was measured via doubly labelled water over a fourteen-day assessment period. Resting metabolic rate was measured and physical activity level calculated. Dietary intake was reported via Snap-N-Send over a non-consecutive ten-day assessment period, alongside changes in fasted body mass and hydration status. Accordingly, energy balance was inferred. The mean (standard deviation) difference between total energy intake (16.73 (1.32) MJ.day-1) and total energy expenditure (18.36 (3.05) MJ.day-1) measured over the non-consecutive ten-day period was unclear (-1.63 (1.73) MJ.day-1; ES = 0.91 ± 1.28; p = 0.221). This corresponded in a most likely trivial decrease in body mass (-0.65 (0.78) kg; ES = 0.04 ± 0.03; p = 0.097). Resting metabolic rate and physical activity level across the fourteen-day pre-season period was 11.20 (2.16) MJ.day-1 and 1.7 (0.2), respectively. For the first time, this study utilises gold standard assessment techniques to elucidate the distinctly large energy expenditures of professional young rugby league players across a pre-season period, emphasising a requirement for equally large energy intakes to achieve targeted body mass and composition adaptations. Accordingly, it is imperative that practitioners regularly assess the energy balance of professional young collision-sport athletes to ensure their unique energetic requirements are achieved.